Herpesvirus reactivation in respiratory tract is associated with increased mortality of severe pneumonia patients and their respiratory microbiome dysbiosis - Liu, Yongan; Wen, Zhenliang; Fang, Yuan; Wang, Tao; Wu, Fengsheng; Zhang, Hongming; Chen, Dechang; Liu, Jiao (Frontiers in Cellular and Infection Microbiology, 2023)
Severe pneumonia (SP) is a respiratory tract disease that seriously threatens human health. The herpesvirus detected in patients, especially with severe and immunodeficient diseases, is gradually attracting the attention of clinical doctors. However, little is known about the effect of herpesvirus on the prognosis of SP patients and the pulmonary microbial community. Here, we retrospectively analyzed respiratory samples from 45 SP patients detected by metagenomic next-generation sequencing (mNGS). A total of five types of herpesviruses were detected, with Human alphaherpesvirus 1 (HHV-1) in 19 patients, Human betaherpesvirus 5 (CMV) in 7 patients, Human betaherpesvirus 7 (HHV-7) in 6 patients, Human alphaherpesvirus 2 (HHV-2) in 5 patients, and Human gammaherpesvirus 4 (EBV) in 4 patients. Further analysis showed that the mortality of the herpesvirus-positive group was significantly higher than that of the negative group. The results also showed that HHV-1 was significantly associated with the prognosis of SP patients, while the other herpesviruses did not have a significant difference in patient mortality. A comparison of the microbial community characteristics of SP patients showed a significant difference in betadiversity between herpesvirus-positive and negative groups. Species difference analysis showed that the herpesvirus-positive group was related to more conditional pathogens, such as Pneumocystis jirovecii and Burkholderia cepacia. In summary, our results suggest that the presence of herpesvirus is associated with the mortality of SP patients. Furthermore, enrichment of conditional pathogens in the respiratory tract of herpesvirus-positive SP patients may be a potential reason for the increased mortality.